Analysis of the Qur’anic Exegesis on the Names and Attributes of Allah (a Comparative Study of Al-Zamakhshari’s Interpretation in Tafsîr Al-Kashshâf and Ibn Taymiyyah’s In Al-Tafsîr Al-Kabîr) - Suatpandy, Bambang Deny (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study analyzes the methodological divergence in interpreting the Qurʾānic names and attributes of God (asmāʾ wa ṣifāt) between al-Zamakhsharī’s al-Kashshāf and Ibn Taymiyyah’s tafsīr corpus, with special reference to the verse of istiwaʾ (Q 20:5) and its implications for Islamic monotheism (tawḥīd). Using a qualitative, descriptive–analytical design, it conducts close textual readings of primary works, a targeted comparison of the istiwaʾ verse, source triangulation with authoritative tafsīr, and an examination of the linguistic, theological, and historical contexts that shape each method. Findings reveal a clear polarity: al-Zamakhsharī privileges metaphorical–linguistic taʾwīl, construing istiwaʾ as a metaphor for divine sovereignty to safeguard tanzīh (transcendence) and avoid anthropomorphism; Ibn Taymiyyah adheres to the apparent (ẓāhir) sense while affirming bilā kayf (without inquiring “how”), rejecting figurative taʾwīl on the grounds that it risks taʿṭīl (nullification of meaning). Both emphatically repudiate tashbīh (likening God to creation), yet their criteria diverge, yielding distinct theological trajectories: for al-Zamakhsharī, tawḥīd is secured by deconstructing literalism; for Ibn Taymiyyah, it is secured by unwavering submission to transmitted reports (naql) and by treating the dismissal of the apparent meaning as deviation. These approaches have shaped subsequent currents: al-Zamakhsharī’s method informs modern ethical–transcendental readings (e.g., Fazlur Rahman, Asma Barlas, Nurcholish Madjid), whereas Ibn Taymiyyah’s stance undergirds Salafī exegesis (e.g., al-Qāsimī, al-Jazāʾirī, Abdul Hakim Abdat) as a guardrail against interpretive relativism. The study concludes that Ibn Taymiyyah’s method better preserves the integrity of revelation while maintaining divine transcendence. More broadly, this divergence crystallizes a durable split within tafsīr epistemology, between linguistic rationalism and textual purity, with lasting consequences for articulating tawḥīd in Islamic thought.